2015
DOI: 10.1016/j.molonc.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Blood circulating tumor DNA for non‐invasive genotyping of colon cancer patients

Abstract: Most solid tumors, including colorectal cancers, shed cell-free DNA (ctDNA) in the blood. ctDNA can be analyzed to generate molecular profiles which capture the heterogeneity of the disease more comprehensively then tumor tissue biopsies. This approach commonly called 'liquid biopsy' can be applied to monitor response to therapy, to assess minimal residual disease and to uncover the emergence of drug resistance. This review will discuss current and future developments of ctDNA analysis in the clinical manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…Strickler and colleagues recently reported cell-free DNA genomic profiling results for over 1,000 colorectal carcinoma patients, but analysis was largely focused on short variant alterations, and no comparison with paired tissue samples was available (22). Alternative applications for ctDNA, including detection of residual disease and early recurrence, rather than identification of actionable GAs, have been the focus of other studies and are not formally examined in our analysis (35, 36). Despite the promise of ctDNA, there are clear disadvantages in relying solely on ctDNA testing, including lack of sufficient ctDNA in approximately 18% of samples, low purity (MSAF) of ctDNA, which can lead to diminished ability to reliably detect gene amplifications, and overall smaller gene panels with ctDNA versus tissue, which limit the total number of assessable alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Strickler and colleagues recently reported cell-free DNA genomic profiling results for over 1,000 colorectal carcinoma patients, but analysis was largely focused on short variant alterations, and no comparison with paired tissue samples was available (22). Alternative applications for ctDNA, including detection of residual disease and early recurrence, rather than identification of actionable GAs, have been the focus of other studies and are not formally examined in our analysis (35, 36). Despite the promise of ctDNA, there are clear disadvantages in relying solely on ctDNA testing, including lack of sufficient ctDNA in approximately 18% of samples, low purity (MSAF) of ctDNA, which can lead to diminished ability to reliably detect gene amplifications, and overall smaller gene panels with ctDNA versus tissue, which limit the total number of assessable alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, most cancers shed cell-free circulating tumor DNA (ctDNA) in the blood[30]. ctDNA can be analyzed to generate molecular profiles which capture the heterogeneity of the disease more comprehensively then tumor tissue biopsies.…”
Section: Liquid Biopsies: Circulating Tumor Cells and Circulating Tummentioning
confidence: 99%
“…It has also been reported that liquid biopsies can be used for KRAS mutation analysis in colon cancer and BRAF mutation analysis in melanoma (72,73).…”
Section: Key To Success In Molecular Processes: Communicationmentioning
confidence: 99%
“…Obtaining genetic material from both the primary tumor and metastatic deposits at the same time may be of benefit in our understanding of tumor heterogeneity (123). At this stage, sequential administration of CTC analyzes before, during, and after treatment can provide information about tumor progression and possible resistance mechanisms (73,124,125). …”
mentioning
confidence: 99%